2010
DOI: 10.1038/onc.2010.197
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of 15-lipoxygenase 2 (15-LOX2) in mouse prostate leads to hyperplasia and cell senescence

Abstract: 15-Lipoxygenase 2 (15-LOX2), a lipid-peroxidizing enzyme, is mainly expressed in the luminal compartment of the normal human prostate and often decreased or lost in prostate cancer. Previous studies from our lab implicate 15-LOX2 as a functional tumor suppressor. To better understand the biological role of 15-LOX2 in vivo, we established prostate-specific 15-LOX2 transgenic mice using the ARR2PB promoter. Unexpectedly, transgenic expression of 15-LOX2 or 15-LOX2sv-b, a splice variant that lacks the arachidonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 51 publications
4
63
0
Order By: Relevance
“…Moreover, increased expression of 15-LOX2 in RCC, particularly in TAMs, was associated with elevated production of immunosuppressive and proinflammatory factors. Emerging evidence indicates that expression of 15-LOX2 in human macrophages could be upregulated by hypoxia (34), whereas transgenic overexpression of this enzyme in prostate tissue promotes hyperplasia (35). We speculate that in contrast to inflammation-resolving function of 15-LOX1, expression of 15-LOX2 in tumor microenvironment could be associated with cancer-related chronic inflammation and local immunosuppression.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, increased expression of 15-LOX2 in RCC, particularly in TAMs, was associated with elevated production of immunosuppressive and proinflammatory factors. Emerging evidence indicates that expression of 15-LOX2 in human macrophages could be upregulated by hypoxia (34), whereas transgenic overexpression of this enzyme in prostate tissue promotes hyperplasia (35). We speculate that in contrast to inflammation-resolving function of 15-LOX1, expression of 15-LOX2 in tumor microenvironment could be associated with cancer-related chronic inflammation and local immunosuppression.…”
Section: Discussionmentioning
confidence: 91%
“…To determine whether 15-LOX2 truly possesses (prostate) tumor-suppressive functions in vivo, we have recently generated prostate-specific transgenic (Tg) mice using the ARR2Pb promoter 17 to drive the expression of full-length (fl) 15-LOX2 or, for comparison, 15-LOX2 splice variant b (15LOX2-svb) that lacks enzymatic activity 18 . Three 15-LOX2 (fl2, fl15, fl26) and 3 15LOX2-svb (svb9, svb10, svb15) Tg lines were established that exhibited various levels of transgene expression 18 .…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether 15-LOX2 truly possesses (prostate) tumor-suppressive functions in vivo, we have recently generated prostate-specific transgenic (Tg) mice using the ARR2Pb promoter 17 to drive the expression of full-length (fl) 15-LOX2 or, for comparison, 15-LOX2 splice variant b (15LOX2-svb) that lacks enzymatic activity 18 . Three 15-LOX2 (fl2, fl15, fl26) and 3 15LOX2-svb (svb9, svb10, svb15) Tg lines were established that exhibited various levels of transgene expression 18 . Subsequent characterizations and functional studies in fl26 and svb9 lines revealed 2 surprising findings: macroscopically, the fl26, and, in particular, the svb9 Tg prostates, were larger than the age-matched wild-type (WT) prostates; and microscopically, the fl26 prostates, and, less obviously, svb9 prostates, showed hyperplasia, which did not progress to PIN (prostate intraepithelial neoplasia) or adenocarcinoma 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that following severe airway injury, when the blood supply may be interrupted and glucose supply is low, ALDH hi ABSCs may utilize AA in the local environment to facilitate proliferation for repair. Interestingly, the overexpression of lipoxygenase-15 in transgenic mice resulted in hyperplasia of prostate basal cells [41]. Further, lipoxygenases-12e and 15 have been linked to epithelial proliferation in corneal repair after injury [42].…”
Section: Discussionmentioning
confidence: 99%